DETERMINE THE ZARNOSHEH FAULT SITUATION , SANANDAJ-SIRJAN ZONE, IRAN (Global Journal of Advanced Engineering Technologies and Sciences, 2014)
In the past few years, construction extended extraordinarily to the northeast of Arak, Iran, where is an active sedimentary plain in the view of seismicity . The existence of active fault zone represents a hazard for such new urban areas. Therefore, it is important to know the size and position of fault zones before Building or reconstruction development. Recently, detecting fault zone using geophysical surveys has become common. In this paper, both geoelectric-resistivity using a schlomberger array and structural geology have been applied to the Arak plain . These studies revealed that the zarnosheh fault zone has dip-slip component (normal) in addition to having sinestral strike-slip component